Comparison of the acupuncture manipulation properties of traditional East Asian medicine and Western medical acupuncture - Da-Eun Yoon; In-Seon Lee; Younbyoung Chae (Integrative Medicine Research)
Background: Acupuncture treatments frequently use manipulation techniques. The therapeutic advantages of acupuncture differ depending on the acupuncture manipulation. The purpose of this article was to compare manipulation techniques in traditional East Asian medicine (TEAM) and Western medical acupuncture (WMA). Methods: Manipulation techniques in TEAM and WMA were compared according to purpose, modulating parameters, and indications. The practical understanding of manipulation in terms of acupuncture stimulation intensity was also explored. The TEAM manipulation techniques of twirling and lifting and thrusting are discussed in terms of the objectives of tonification and sedation. Results: The main therapeutic effect of WMA is mediated through activation of the nervous system, which is achieved with adequate intensity of needling. The TEAM tonification and sedation techniques were designed to produce mild or intense stimulation, respectively, to elicit varying degrees of deqi sensation. Conclusions: Further research is needed to clarify the differences between the TEAM and WMA practices, and to determine whether different needling manipulations affect treatment outcomes.